Conquering barriers: how formerly incarcerated Black men define and achieve success in higher education - Moore, Heather Dawn (Kansas State University, 2023)
This grounded theory study applies both critical race theory and anti-deficit frameworks to recognize the systemic barriers that are in place to limit the success of formerly incarcerated Black students and challenges anti-deficit perspectives that fault those affected by oppressive systems rather than the systems themselves. This qualitative study used open-ended semi-structured interviews to learn how formerly incarcerated Black men defined and achieved postsecondary academic success. Participants described success in relation to goal achievement and discussed that internal motivation to reach their goals was one of two essential criteria for being academically successful. The other criterion for their success is having support to overcome unique challenges related to being formerly incarcerated. This study adds to the literature to build the knowledge and insight of this underserved student group and urges campuses to consider the educational human right in providing access and support for these students as both a societal obligation to open opportunities for formerly incarcerated people and to welcome diverse populations to their campuses by providing intentional support and access to academic success.
Keywords: Formerly incarcerated; Higher education; Success; Grounded theoryQualitative